1981
DOI: 10.1002/qua.560190210
|View full text |Cite
|
Sign up to set email alerts
|

Mapping between local potentials and ground state densities

Abstract: AbstractsThe mapping between the local one-body potential and the ground state density is discussed. The role of degenerate ground states, which form a set of measure zero in potential space, is shown to be amplified by the unitary transformation between degenerate densities, forming a space filling set in density space. A numerical experiment demonstrating these features is carried out. No indication of non-V representable densities is encountered.On discute la correspondance entre le potentiel local B un cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
(3 reference statements)
1
17
0
Order By: Relevance
“…As is easily seen, in this case all E-V densities are PS-V representable. (This is no longer valid for the state space R-4) Thus we can confirm this conjecture from [25]. But for state spaces larger than C4 the fermion systems can possess a higher degeneracy and then, as mentioned above, Levy [12] and Lieb [7] showed that PS-V and E-V representability no longer coincide.…”
Section: 'V-representabilitysupporting
confidence: 61%
“…As is easily seen, in this case all E-V densities are PS-V representable. (This is no longer valid for the state space R-4) Thus we can confirm this conjecture from [25]. But for state spaces larger than C4 the fermion systems can possess a higher degeneracy and then, as mentioned above, Levy [12] and Lieb [7] showed that PS-V and E-V representability no longer coincide.…”
Section: 'V-representabilitysupporting
confidence: 61%
“…Hence, it can be regarded in the form (6.2-8) with 1/;i = 1l'(Xi), i = 1,2, ... , \I. In order to investigate the nature of mapping between ground-state d ~nsities and local external potentials, let us consider the three-dimensional model system of two noninteracting electrons with 1-1=4 as "the smallest system which is not obviously trivial" (Katriel et al, 1981b). (6.2-27), differs slightly, through the denominator, from that given by Eq.(6.2-5).…”
Section: V-representability Of One-electron Densitiesmentioning
confidence: 99%
“…Katriel et al (1981b) Repeating this procedure many times, this three-dimensional array of the density space may be covered in such a way that some (accesible or A-type) regions are covered in an essentially uniform manner and the other (inaccesible or I-type) ones remain entirely forbidden (see Figure 6.2). In this way, one can choose the off-diagonal elements of the Ho-matrix once and for all for the whole Ho-familv of trial Hamiltonians.…”
Section: =1mentioning
confidence: 99%
See 2 more Smart Citations